146 The Lived Experience of Carer Resilience Told by Carer Advocates. (16th September 2019) - Reid, Laura; Harmon, Aisling
Abstract: Background: Established in 2013 this network of volunteer family carers is a national advocacy group that presents a vital opportunity for carers to use their voice to raise awareness of issues affecting families living with dementia in Ireland. The network is facilitated by a dementia specific service provider. These carer advocates wish to present on a piece of qualitative research they have recently conducted on the topic of carer resilience at the advanced stages of caring for a loved one with dementia. Methods: There are 43 family carer advocates on the network, all of whom were invited to participate in this research. The piece of qualitative research conducted by the network with its members took the form of a questionnaire. The research sought to ascertain how informed and supported carers felt as their loved ones transitioned to long term residential care and the stage thereafter. This research did not discuss the level of professional care given to their loved one but what supports and services were offered to the carer at that time and how this affected their resilience. The aspect of caring for a loved one availing of hospice care naturally emerged during the research process and this topic was also explored in relation to carer resilience. Completed questionnaires were analysed to show findings and draw conclusions. Results: The research gives insight into the lived experience of carer resilience told by carer advocates. The results show that carer advocates feel ill-informed and badly supported as their loved one transitions to or resided in long term residential care. The research also showed that carers feel more informed and supported if their loved one availed of hospice care rather than long term residential care. Conclusion: Carers are not properly informed or supported when their loved one transitions to or resides in long term residential care and this negatively affects their resilience.